2018
DOI: 10.4236/ajac.2018.99031
|View full text |Cite
|
Sign up to set email alerts
|

Shift in pKa of 1,10-Phenanthroline in TBAB and PEG-400 Micellar Media: A Potentiometric Study

Abstract: The acid-base equilibrium of 1,10-phenanthroline (1,10-phen) in the presence of polyethylene glycol 400 (PEG-400, non-ionic) and tetrabutylammonium bromide (TBAB, ionic) micellar media has been studied by Calvin-Wilson titration technique at different mole fractions (0.5%-2.5%) of PEG-400 and TBAB micellar solutions at an ionic strength of 0.16 mol dm −3 NaCl and at a temperature of 298 K. The pH metric data were subjected to SCPHD program to obtain correction factor and K w which were given as initial inputs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…For a reliable determination of stability constants corresponding to mixed ligand model complexes, pooled data re nement of all the experimental trial using MINIQUAD75 computer program was chosen. The results of the free acid correction factor, values of Kw, protonation constants of the ligands [22] and binary M-L complex constants [26] were xed and used as initial imputes in the analysis of the mixed ligand complexes using MINIQUAD75 program [33][34] with inbuilt statistical parameters of chemical model re nement tools.…”
Section: Instruments and Methods Of Titrationsmentioning
confidence: 99%
See 3 more Smart Citations
“…For a reliable determination of stability constants corresponding to mixed ligand model complexes, pooled data re nement of all the experimental trial using MINIQUAD75 computer program was chosen. The results of the free acid correction factor, values of Kw, protonation constants of the ligands [22] and binary M-L complex constants [26] were xed and used as initial imputes in the analysis of the mixed ligand complexes using MINIQUAD75 program [33][34] with inbuilt statistical parameters of chemical model re nement tools.…”
Section: Instruments and Methods Of Titrationsmentioning
confidence: 99%
“…1,10-Phenanthroline (Phen) is bidentate hetrocyclic ligand having two electron donor N-atoms to the vacant shell of transition metal ions [19,20]. Studies have also revealed that Phen forms both binary and mixed ligand complexes with a number of metal ions in wide pH ranges [6,[19][20][21][22]. It is capable of forming stable metal complexes of even lower oxidation states [10,23,24] in mixed ligand system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…nature and extent of formation of species as a function of pH can be obtained from speciation study [7,8].…”
Section: Mononuclear Binary Complex Formation Equilibria Of L-ornithimentioning
confidence: 99%